Reclaiming the value of qualitative analysis in sports performance research - Spyridon Plakias (Physical Education and Sports: Studies and Research, 2026)
Quantitative metrics and technology-driven approaches have reshaped sports performance analysis (SPA), yet they risk overshadowing the equally vital contribution of qualitative methods. This opinion paper highlights the value of qualitative analysis in capturing the complexity, context, and meaning of player and team behaviors, elements that numbers alone cannot explain. Drawing on video-based evaluations, case studies, and narrative reconstructions, qualitative approaches provide insights into tactical, psychological, and interactional dimensions of performance that are indispensable for bridging the science–practice gap. By integrating qualitative and quantitative perspectives, SPA can achieve a more balanced and applicable paradigm, ensuring that scientific research remains relevant to real-world coaching and athlete development. This paper calls for a renewed recognition of qualitative methods as a central pillar of SPA and invites further scholarly contributions to this evolving discussion.